Implementation of the Project on Strengthening the Profile of Pancasila Students Based on Ado Local Wisdom to Improve Social Emotional Skills of 5-6 Year Old Children at TKK St. Gabriel Satap Mangulewa - Wonga, Maria Susanti; Efrida Ita; Andi Nafsia; Elisabeth Tantiana Ngurah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to determine the implementation of the Project for Strengthening the Profile of Pancasila Students Based on Ado Local Wisdom to Improve the Social Emotional Capabilities of Children Aged 5-6 Years at TKK St. Gabriel Satap Mangulewa in the 2024/2025 academic year. The type of research used is descriptive qualitative research using data collection methods, namely interviews, documentation and observation. The informants in the research were the school principal and class teacher. The data analysis technique uses Miles and Huberman with the implementation stages of data collection, data reduction, data presentation and drawing conclusions. The results of research at TKK St. Gabriel saw Mangulewa, that through the local wisdom game ado in the implementation of the project to strengthen the profile of Pancasila students, it showed that the social emotional abilities of children aged 5-6 years had improved well, seen from the observation process at the start of the learning activity, implementation usingthe ado game media, until the end learning.